A Systematic Review of DURAL Puncture Epidural Analgesia for Labor. Issue 1 (March 2019) - Layera, S.; Bravo, D.; Aliste, J.; Tran, Q.
Abstract : ( J Clin Anesth . 2019;53:5–10) Combined spinal epidural analgesia (CSEA) has the benefit of shorter onset time, decreased motor blockade, and more reliable analgesia. However, intrathecal local anesthesia (LA) injection may obscure the response of the test dose used to exclude inadvertent subarachnoid placement of the epidural catheter. Dural puncture epidural analgesia (DPEA), in which no LA is deposited in the subarachnoid space, is a potential means of labor analgesia that avoids this effect. Benefits of DPEA remain unproven. In this systematic review, authors discussed the evidence available from randomized controlled trials and compared DPEA and lumbar epidural analgesia (LEA) for labor analgesia.